Horizontal distribution of intertidal nematode from Sabah, Malaysia - Mohd Long, Shabdin; Haji Ross, Othman (Universiti Malaysia Sabah, 2008)
The aim of this study is to determine the horizontal distribution of nematodes species density, species diversity and feeding types on the intertidal area of Lok Kawi beach, Sabah, Malaysia. The approach taken was to sample the nematodes and measured selected parameters of the hole water from high-water to low-water marks. The results show that the nematode feeding type non selective deposit feeders (1B) and epigrowth feeders (2A) groups, species diversity, evenness, species richness and species number increased towards the low tide level. The height of the beach did not clearly show their influence on the horizontal distribution of the nematodes. Pearson correlation coefficient shows that there is a significant correlation (R = 0.64, p < 0.05) between the height of the beach and the species diversity of the nematodes. However, the cluster and factor analysis of the stations did not show clearly about the influence of height of the beach on nematodes densities. Therefore, we conclude that there were no definite and universal causative factors, which controlled the horizontal distribution of nematodes species diversity in the intertidal sandy and muddy habitats of the Lok Kawi beach, Sabah.